2007
DOI: 10.1093/carcin/bgm252
|View full text |Cite
|
Sign up to set email alerts
|

Long-term tracking of hepatitis B viral load and the relationship with risk for hepatocellular carcinoma in men

Abstract: Little is known about the longitudinal course of hepatitis B virus (HBV) load and its relationship with the development of hepatocellular carcinoma (HCC). We conducted a case-cohort study nested within a cohort of 2874 HBV surface antigen-positive male Taiwanese government employees aged 30 years or older. HBV genotype and DNA levels (i.e. viral load) were tested using polymerase chain reaction-based assays on plasma samples from 112 cases and 1031 non-cases. Prediagnostic plasma levels of HBV DNA were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(111 citation statements)
references
References 20 publications
4
107
0
Order By: Relevance
“…This is largely influenced by the HBV genotype and host immune status. Previous studies have demonstrated that the presence of HBeAg and persistently high serum HBV DNA levels are risk factors for the occurrence of cirrhosis and HCC [12][13][14] . Moreover, chronic infection with HBV genotype C is more likely to cause liver cirrhosis than genotype B [15] .…”
Section: Antiviral Therapy and Prevention Of Hbv-related Hccmentioning
confidence: 99%
“…This is largely influenced by the HBV genotype and host immune status. Previous studies have demonstrated that the presence of HBeAg and persistently high serum HBV DNA levels are risk factors for the occurrence of cirrhosis and HCC [12][13][14] . Moreover, chronic infection with HBV genotype C is more likely to cause liver cirrhosis than genotype B [15] .…”
Section: Antiviral Therapy and Prevention Of Hbv-related Hccmentioning
confidence: 99%
“…Firstly, HBV is hepatotropic viruses, and it has been documented that HBV infection have clinically and histologically more severe liver disease and higher risk of HCC and cirrhosis. 25,26 The possible explanation why HBV infection did not correlate with CKD, proteinuria, or low eGFR may be related to the competing risk of death. Secondly, the immune response to HBV is present only in patients with active hepatitis B, and this response plays a role in both hepatitis B and HBV associated nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted among Taiwan population demonstrated that if the HBV load is greater than 105 copies/ml, the odd ratio for HCC risk would reach 2.5 (95%CI=1.1-5.7), furthermore, the author also observed a lower odd ratio of 2.3 between HCC risk and HBV load among noncirrhotic hepatocellular carcinoma patients . A case-cohort study in Taiwan revealed that high viral load can cause HCC and low viral load (<4.39 log copies/ml) was associated with sustained normalization of ALT levels and decreased risk of this disease (Wu et al, 2008). Similarly, a research performed in Hong Kong (Chan et al, 2008) also reported positive association between high HBV load and HCC risk with a hazard ratio of 1.62 among Hong Kong population.…”
Section: Hbv Infectionmentioning
confidence: 95%